Peranan rizobakteri dan fungi mikoriza arbuskular dalam proses fotosintesis dan produksi gula sorgum manis (Sorghum bicolor L. Moench) Role of rhizobacteria and arbuscular mycorrhizal fungi in increasing photosynthesis process and sugar production of sweet sorghum (Sorghum bicolor L. Moench) - Bedah RUPAEDAH; Iswandi ANAS; Dwi Andreas SANTOSA; Wahono SUMARYONO; Sri Wilarso BUDI (Menara Perkebunan, 2015)
AbstractDual inoculation effects of rhizobacteria andAMF as well as the addition of chemical fertilizerson photosynthesis were studied by analyzingprocess of CO2 gas exchange, chlorophyll content,nutrient uptake, sugar content and growth of sweetsorghum. AMF inoculation as a single cultureincreased carbon assimilation, stomatal conductance,intercellular CO2 concentration, phosphoruscontent, chlorophyll content, sugar content, plantheight, shoot weight and mycorrhizal colonization.Interaction of AMF and rhizobacteria increasedsugar content of sweet sorghum stems andpotassium content of sweet sorghum leaves,whereas its interaction with chemical fertilizerssignificantly increased chlorophyll content, sugarcontent and mycorrhizal colonization of sorghumplant roots. Interaction of AMF, rhizobacteria andchemical fertilizers increased sugar content, rootweight and mycorrhizal colonization. The use ofAMF solely or its interaction with rhizobacteriaand chemical fertilizers had a great potential inimproving photosynthesis process of sweetsorghum. The process is associated with increasingcrop productivity, such as sugar content ofsorghum which is potential as a source ofrenewable energy.AbstrakPengaruh inokulasi ganda rizobakteri danFMA dengan penambahan pupuk kimia dipelajaridengan cara menganalisis proses pertukaran gas CO2, kandungan klorofil, kandungan hara dan gula,pertumbuhan dan produktivitas sorgum manis.Inokulasi FMA sebagai kultur tunggal dapatmeningkatkan asimilasi karbon, konduktansistomata, konsentrasi CO2 interselular, kandunganfosfor, kandungan klorofil, kandungan gula, tinggitanaman, berat batang dan derajat kolonisasimikoriza. Interaksi antara rizobakteri dan FMAdapat meningkatkan kandungan gula batang dankalium daun sorgum manis, sedangkan interaksinyadengan pupuk kimia dapat meningkatkan kandunganklorofil dan gula serta derajat kolonisasimikoriza pada perakaran sorgum manis. Sementaraitu, interaksi FMA, rizobakteri dan pupuk kimiadapat meningkatkan kandungan gula batang, beratakar dan derajat kolonisasi mikoriza pada perakaransorgum manis. Penggunaan FMA baik sendirimaupun interaksinya dengan rizobakteri dan pupukkimia memiliki potensi besar dalam meningkatkanproses fotosintesis sorgum manis. Proses tersebutberkaitan dengan peningkatan produktivitas sorgummanis dalam hal ini kandungan gula sorgum manisyang berpotensi sebagai sumber energi terbarukan.